The great St. Louis bank robbery - Guggenheim, Charles; Stix, John, 1920-2004; McQueen, Steve, 1930-1980; Columbia Broadcasting System, inc.; Mill Creek Entertainment; OverDrive, Inc.; Cinetel Films ([Hollywood, CA] : Columbia Broadcasting System, Inc., 1959)
Portrays four criminals who plan a bank robbery amidst their frustrations and jealousies. A psychological drama based on an actual crime and filmed in the same setting where it occurred.
Steve McQueen, Crahan Denton, David Clarke, James Dukas, Molly McCarthy.
Director of photography, Victor Duncan; editor, Warren Adams; music, Bernardo Segall.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 9, 2015)
Keywords: Bank robberies -- Drama; Thrillers (Motion pictures); Feature films; Film noir; Caper films; Gangster films; Internet videos; Streaming video